2015
DOI: 10.3390/md14010004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparison of the Structural Features, Immune-Modulatory and Anti-Avian Influenza Virus Activities Conferred by Three Algal Sulfated Polysaccharides

Abstract: Three marine macroalgae, i.e., Grateloupia filicina, Ulva pertusa and Sargassum qingdaoense, were selected as the deputies of Rhodophyta, Chlorophyta and Ochrophyta for comparative analysis of the molecular structures and biological activities of sulfated polysaccharides (SP). The ratio of water-soluble polysaccharides, the monosaccharide composition and the sulfated contents of three extracted SPs were determined, and their structures were characterized by Fourier transformation infrared spectroscopy. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 87 publications
2
44
0
1
Order By: Relevance
“…The presence of absorbance near 840 cm −1 reflects the presence of β‐glycoside‐type binding . Furthermore, the result of monosaccharide composition confirms that PS is a heteropolysaccharides composed of different monosaccharide units and chains, this is in accordance with previous findings that recorded the presence of rhamnose, xylose, and gluconic acid, but did not report the presence of lactose and fucose . The chromatograph of the PS from U. lactuca is composed essentially by two principal peaks with MWs less than 500 kDa.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The presence of absorbance near 840 cm −1 reflects the presence of β‐glycoside‐type binding . Furthermore, the result of monosaccharide composition confirms that PS is a heteropolysaccharides composed of different monosaccharide units and chains, this is in accordance with previous findings that recorded the presence of rhamnose, xylose, and gluconic acid, but did not report the presence of lactose and fucose . The chromatograph of the PS from U. lactuca is composed essentially by two principal peaks with MWs less than 500 kDa.…”
Section: Discussionsupporting
confidence: 90%
“…43 Furthermore, the result of monosaccharide composition confirms that PS is a heteropolysaccharides composed of different monosaccharide units and chains, this is in accordance with previous findings that recorded the presence of rhamnose, xylose, and gluconic acid, but did not report the presence of lactose and fucose. [44][45][46][47] The chromatograph of the PS from U. lactuca is composed essentially by two principal peaks with MWs less than 500 kDa. This might be an advantage as it has been reported that low-molecular-weight PS are more effective than high-molecular-weight PS at enhancing immunity, 48 Indeed, PS from several ulvans have been used as drug carriers, as well as in wound dressings and tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…The polysaccharide yield was 4.4 (% w / w dry biomass basis), nearest to the values reported in the diatom Gomphonema olivaceum (3% w / w ) [7] and in the benthic seaweed Sargassum qingdaoense (7.2% w / w ) [8], but lower than the values reported for the planktonic specie Spirulina platensis (13.6% w / w ) [9]. These differences could be due to the extraction methods used and/or the type of species investigated.…”
Section: Resultssupporting
confidence: 59%
“…The marine sourced sulfated polysaccharides have established anti-oxidative, antimicrobial, anticoagulant, and anticancer activities (Freudenberg et al, 2015; Song et al, 2015; Fernando et al, 2016; Prasedya et al, 2016; Wang et al, 2017). Biomaterial developed here capitalizes on the favorable properties of these individual components to regulate microenvironment thereby acting synergistically to promote healing.…”
Section: Discussionmentioning
confidence: 99%